Aggregating the results of ranking models in data envelopment analysis by Shannon's entropy: a case study in hotel industry. (1st January 2013) - Shirouyehzad, Hadi; Lotfi, Farhad Hosseinzadeh; Dabestani, Reza
Ranking as one of the main issues in data envelopment analysis has been extensively analysed by scholars and practitioner. During the last three decades, a large number of ranking models have been proposed. However, these models do not necessarily present a unique result for the similar problems. Therefore, it is very important to achieve a more reliable result in ranking problem. In this paper, an aggregate method base on the Shannon's entropy is proposed in order to integrate dissimilar ranking results. This method is not depended on the type of ranking methods. By applying the proposed method, decision makers and managers can achieve a more reliable decision than the method which is based on a single ranking method. To prove the applicability of the proposed method, it is examined in 12 hotels in Isfahan as a historical city in Iran.